Applied consumption analysis - Phlips, Louis (Amsterdam : North-Holland Pub. Co. ; New York : American Elsevier Pub. Co., 1974)
This volume links the abstract theory of demand with its econometric implementation. Exercises lead the reader from elementary utility maximization to the most sophisticated recent techniques, highlighting the main steps in the historical evolution of the subject. The first part presents a brief discussion of duality and flexible forms, and in particular of Deaton and Muellbauer's ``almost ideal demand system''. Part two includes the author's work on true wage indexes, and on inter temporal utility maximization.
Includes index.
Bibliography: p. 265-274.
rpm 01/08/2017
Loans
Keywords: Demand (Economic theory); Consumption (Economics); Statics and dynamics (Social sciences)